Cladistic analysis of the subfamily Arsenurinae (Lepidoptera, Saturniidae) based on adult morphology - de Camargo, Amabílio J. A.; Mielke, Olaf H. H.; Casagrande, Mirna M. (Zootaxa, 2009)
The family Saturniidae is distributed on all continents except polar areas, and includes about 1528 species in 162 genera, being the group with the largest diversity among Bombycoidea. Approximately 970 species are known from the New World. However, recent molecular studies indicate 1861 species in 162 genera and nine subfamilies. The family Arsenurinae consists of 63 species distributed exclusively in ten Neotropical genera, with phylogenetic relationships poorly understood. The goal of this study was to test the monophyly of the subfamily, tribes and genera using cladistic analysis of adult morphological characters. The subfamily, tribes and genera were all recovered as monophyletic groups with the following relationships among genera: (Almeidaia ((Loxolomia, Copiopteryx) ((Rhescyntis) ((Grammopelta, Arsenura) ((Caio) ((Dysdaemonia, Titaea) Paradaemonia)))))). Both tribes, Arsenurini and Almeidaiini, share several characters, but morphological study of Almeidaiini demonstrates that it also presents significant differences.